Constructing "quantized quorums" to guide emergent phenotypes through quorum quenching capsules. Issue 2 (9th December 2016) - Zargar, Amin; Quan, David N.; Abutaleb, Nadia; Choi, Erica; Terrell, Jessica L.; Payne, Gregory F.; Bentley, William E.
ABSTRACT: Microbial cells have for many years been engineered to facilitate efficient production of biologics, chemicals, and other compounds. As the "metabolic" burden of synthetic genetic components can impair cell performance, microbial consortia are being developed to piece together specialized subpopulations that collectively produce desired products. Their use, however, has been limited by the inability to control their composition and function. One approach to leverage advantages of the division of labor within consortia is to link microbial subpopulations together through quorum sensing (QS) molecules. Previously, we directed the assembly of "quantized quorums, " microbial subpopulations that are parsed through QS activation, by the exogenous addition of QS signal molecules to QS synthase mutants. In this work, we develop a more facile and general platform for creating "quantized quorums." Moreover, the methodology is not restricted to QS‐mutant populations. We constructed quorum quenching capsules that partition QS‐mediated phenotypes into discrete subpopulations. This compartmentalization guides QS subpopulations in a dose‐dependent manner, parsing cell populations into activated or deactivated groups. The capsular "devices" consist of polyelectrolyte alginate–chitosan beads that encapsulate high‐efficiency (HE) "controller cells" that, in turn, provide rapid uptake of the QS signal molecule AI‐2 from culture fluids. In this methodology, instead of adding AI‐2 to parse QS‐mutants into subpopulations, we engineered cells to encapsulate them into compartments, and they serve to deplete AI‐2 from wild‐type populations. These encapsulated bacteria therefore, provide orthogonal control of population composition while allowing only minimal interaction with the product‐producing cell population or consortia. We envision that compartmentalized control of QS should have applications in both metabolic engineering and human disease. Biotechnol. Bioeng. 2017;114: 407–415. © 2016 Wiley Periodicals, Inc. Abstract : A quorum quenching device was constructed by entrapping E. coli cells with enhanced quorum sensing (QS) uptake kinetics inside an alginate–chitosan capsule (left). The QS molecule, AI‐2, enters from the surrounding media into the capsule and is consumed by the entrapped E. coli, which cannot leak out. When these capsules are mixed with planktonic, QS bacteria, subpopulations of varying QS‐activation are formed in the target bacterial population (right). The authors propose these "quantized quorums" as a means to link microbial subpopulations.